Search for conformation of thiosemicarbazone reagents and their complexes with metals by using Monte Carlo and docking simulation - Nguyen Minh Quang; Tran Xuan Mau; Pham Nu Ngoc Han; Pham Van Tat (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên, 2020)
In this study, the conformation of ML2 complexes of new thiosemicarbazone reagents with metal cations Cd2+, Ni2+, Cu2+, Hg2+, Pb2+, Mn2+, and Zn2+ is investigated. The methods include MM+ and PM3 calculations with the Monte Carlo techniques using the Metropolis algorithm in the temperature range of 298–473 K. The initial selection conformation was carried out randomly after 15 repeated conformations, and 30 conformations were rejected. The conformations were chosen to change by changing the torsional-dihedral angles at the position of the metal cation associated with the donor atoms N and S of the thiosemicarbazone reagents. This was performed by randomly changing the dihedral angles to create new structures, and then the energy values of these angles were minimized with the PM3 and MM+ calculation. The lowest suitable energies were accumulated, while high- or duplicate-energy structures were discarded. The docking method was also employed to screen the most suitable metal-thiosemicarbazone complexes that bind to the active site on the SARS-CoV-2 protein. The docking method enabled us to choose the molecular conformation of the most significant Cd2+-thiosemicarbazone complex.